Hypermethylation of the PRKCZ Gene in Type 2 Diabetes Mellitus. (16th March 2013) - Zou, Li; Yan, Shirong; Guan, Xueping; Pan, Yunjun; Qu, Xin
Abstract : Objectives . To study the correlation between the methylation of protein kinase C epsilon zeta (PRKCZ) gene promoters and type 2 diabetes mellitus (T2DM). Methods . The case-control method was implemented in 272 unrelated to one another cases in Shiyan People's Hospital. Of those, 152 were diagnosed as T2DM cases, and the other 120 cases were healthy individuals visiting the hospital for a physical examination. The subjects were first divided into two groups: the T2DM group and the normal control (NC) group. Next, methylated DNA immunoprecipitation chip (MeDIP-chip) was used for detection. Bisulfite sequencing PCR (BSP) and gene sequencing were then performed to detect and analyze the correlation between PRKCZ gene promoter methylation and T2DM. Finally, Western blotting was applied to determine the serum level of PRKCZ. The data were then analyzed with the statistics analyzing software SPSS 17.0. Results . In contrast with cases in NC, T2DM patients showed a high level of methylation, with 7 of 9 CpG sites were shown to be methylated, whereas, in the control group, only one CpG site was found to be methylated. The methylated CpG sites for the two groups showed marked differences (P < 0.01 ). Additionally, the level of PRKCZ was decreased in T2DM subjects, and the difference between the two groups was statistically significant (P < 0.05 ). Discussion . This study suggests that the PRKCZ gene is the hypermethylated gene of T2DM and the hypermethylation PRKCZ gene may be involved in the pathogenesis of T2DM.